Sexuality and relationships in the lives of people with intellectual disabilities : standing in my shoes - Chapman, Rohhss; Ledger, Sue; Townson, Louise; Docherty, Daniel (Jessica Kingsley Publishers, 2015)
Wide-ranging, authoritative and grounded in the expertise of people with intellectual disabilities, this book offers an authentic account of the challenges those with intellectual disabilities face in their relationships and sex lives across the globe and explores what society needs to do to respect their rights.